2014
DOI: 10.1016/j.celrep.2014.08.030
|View full text |Cite
|
Sign up to set email alerts
|

P7C3 Neuroprotective Chemicals Block Axonal Degeneration and Preserve Function after Traumatic Brain Injury

Abstract: SUMMARY The P7C3 class of neuroprotective aminopropyl carbazoles has been shown to block neuronal cell death in models of neurodegeneration. We now show that P7C3 molecules additionally preserve axonal integrity after injury, before neuronal cell death occurs, in a rodent model of blast-mediated traumatic brain injury (TBI). This protective quality may be linked to the ability of P7C3 molecules to activate nicotinamide phosphoribosyltransferase, the rate-limiting enzyme in nicotinamide adenine dinucleotide sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 37 publications
5
99
0
Order By: Relevance
“…Tangential support for this hypothesis includes a study in which deletion of neurofibromin 1 from adult-born cells increased levels of adult neurogenesis and had an antidepressant-like effect on behavior; however, this manipulation not only increased the number of adultborn neurons, but also affected these cells in other ways, such as by activating ERK signaling (Li et al, 2012). More recently, the P7C3 compound has been shown to increase adult neurogenesis and has an antidepressant-like effect on social interaction behavior following social defeat; however, P7C3 likely exerts its effects through multiple biological processes including, but not limited to, neurogenesis (Walker et al, 2014;Wang et al, 2014;Yin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tangential support for this hypothesis includes a study in which deletion of neurofibromin 1 from adult-born cells increased levels of adult neurogenesis and had an antidepressant-like effect on behavior; however, this manipulation not only increased the number of adultborn neurons, but also affected these cells in other ways, such as by activating ERK signaling (Li et al, 2012). More recently, the P7C3 compound has been shown to increase adult neurogenesis and has an antidepressant-like effect on social interaction behavior following social defeat; however, P7C3 likely exerts its effects through multiple biological processes including, but not limited to, neurogenesis (Walker et al, 2014;Wang et al, 2014;Yin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We did see BBB damage 24 h post LFPI, demonstrated by the immunohistochemical staining of mouse IgG at the injury site; additionally, a loss of BBB integrity using the bTBI model occurring within the 24 h post injury has been previously well established 23, 39. There was no visible disruption of the brain architecture at 24 days post blast injury.…”
Section: Discussionmentioning
confidence: 54%
“…There was no visible disruption of the brain architecture at 24 days post blast injury. It has been well documented that the integrity of BBB is reestablished 24 h post blast injury,23, 39but we wanted to verify that overt tissue disruption did not occur. Damage to the BBB in both of these models leads to the loss of the brain's normal immunologic privilege and isolation from the systemic immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the progressive nature of many forms of neuropsychiatric disease, including those linked to CACNA1C, is consistent with neurodegenerative processes that would be amenable to treatment with neuroprotective agents. 46 In this light, it is useful to note that P7C3 compounds have demonstrated protective efficacy in preclinical models of Parkinson disease, 24,[28][29] cognitive decline with aging, 31 amyotrophic lateral sclerosis, 23 traumatic brain injury, [25][26][27] peripheral nerve injury, 22 neurodegeneration-associated depression, 46 and now cell death associated with genetic susceptibility to mental illness. 17 It has recently been reported that P7C3 compounds enhance flux of the nicotinamide adenine dinucleotide (NAD) salvage pathway in normal mammalian cells, and also facilitate NAD recovery following doxorubicin exposure.…”
mentioning
confidence: 99%
“…levels in the brain. To address this problem, we turned to the neuroprotective aminopropyl carbazole compound P7C3-A20, a small molecule that blocks neuronal cell death, [22][23][24][25][26][27][28] thereby increasing the magnitude of hippocampal neurogenesis. [29][30][31] Treatment of forebrain Ca v 1.2 cKO mice with P7C3-A20 restored normal survival of young hippocampal neurons (Fig.…”
mentioning
confidence: 99%